Zinc transporters protein level in postmortem brain of depressed subjects and suicide victims. (December 2016) - Rafalo-Ulinska, Anna; Piotrowska, Joanna; Kryczyk, Agata; Opoka, Włodzimierz; Sowa-Kucma, Magdalena; Misztak, Paulina; Rajkowska, Grazyna; Stockmeier, Craig A.; Datka, Wojciech; Nowak, Gabriel; Szewczyk, Bernadeta
Abstract: Background: Major depressive disorder (MDD) is a serious psychiatric illness, associated with an increasing rate of suicide. The pathogenesis of depression may be associated with the disruption of zinc (Zn) homeostasis. In the brain, several proteins that regulate Zn homeostasis are present, including Zn transporters (ZnTs) which remove Zn from the cytosol. The present study was designed to investigate whether depression and suicide are associated with alterations in the expression of the ZnTs protein. Methods: Protein levels of ZnT1, ZnT3, ZnT4, ZnT5 and ZnT6 were measured in postmortem brain tissue from two different cohorts. Cohort A contained 10 subjects diagnosed with MDD (7 were suicide victims) and 10 psychiatrically-normal control subjects and cohort B contained 11 non-diagnosed suicide victims and 8 sudden-death control subjects. Moreover, in cohort A we measured protein level of NMDA (GluN2A subunit), AMPA (GluA1 subunit) and 5-HT1A receptors and PSD-95. Proteins were measured in the prefrontal cortex (PFC) using Western blotting. In addition, Zn concentration was measured using a voltammetric method. Results: There was a significant increase in protein levels of ZnT1, ZnT4, ZnT5 in the PFC in MDD, relative to control subjects, while ZnT3 protein level was decreased in MDD. There was no significant difference in the Zn concentration in the PFC between control and MDD subjects. Similarly, in the PFC of suicide victims (non-diagnosed), an increase in protein levels of ZnT1, ZnT4, ZnT5 and ZnT6 was observed. Conversely, protein levels of ZnT3 were decreased in both suicide victims and subjects with MDD, in comparison with control subjects. There was also a significant decrease in the protein level of GluA1, GluN2A, PSD-95 and 5-HT1A in MDD. Conclusions: Our studies suggest that alterations in Zn transport proteins are associated with the pathophysiology of MDD and suicide. Highlights: MDD and suicide in associated with alterations of ZnTs protein level in the PFC. Increase in ZnT1, ZnT4 and ZnT5 and decrease in ZnT3 protein was found in MDD. Suicide is associated with increase in ZnT1, 4, 5, 6 and decrease in ZnT3 protein. Total Zn concentration is not changed in PFC of MDD.